Performansi dan Konteks Penuturan Seni Beluk Kampung Adat Cikondang, Pangalengan, Kabupaten Bandung - Tedi Permadi; Mu'afa Audia Permadikusumah (Tambo: Journal of Manuscript and Oral Tradition, 2026)
This study explores the art of beluk in the Cikondang Traditional Village as a crucial instrument for transmitting values, adapting to situations without losing its cultural legitimacy. While studies of traditional arts tend to focus on external aesthetic aspects, this article offers a novel approach through an in-depth analysis of the dialectic between performance structure, participants and role allocation, narrative context, and other components of performance in indigenous communities. Beluk itself is a vocal tradition based on the recitation of wawacan texts characterized by the use of very high vocal registers and complex melismatic techniques. Using qualitative methods and an interpretive thematic approach, this study involved participants from among indigenous community leaders and members. The research findings indicate that beluk narration in ritual contexts is strictly regulated by sacred momentum and customary authority, while in non-ritual contexts it exhibits more pragmatic flexibility. These differences in patterns demonstrate that variations in beluk practices are not solely determined by aspects of narration and musicality, but are closely related to social goals and the maintenance of collective identity. This article makes a theoretical contribution to the study of oral traditions regarding how a folk art maintains its relevance through performance flexibility under a consistent customary framework.